2009
DOI: 10.1038/hr.2008.23
|View full text |Cite
|
Sign up to set email alerts
|

Association of blood pressure levels with the effects of alcohol intake on the vasculature in Japanese men

Abstract: The association of blood pressure levels with the effects of alcohol intake on the vasculature has not been clarified. We evaluated the differential effects of alcohol intake on the vasculature of subjects with optimal or normal blood pressure (ONbp) and those with high normal blood pressure or higher (HNHbp) in a 6-year follow-up study. The pulse wave velocity (PWV) was measured on three occasions at an interval of 3 years in 1185 middle-aged Japanese men (age 41±8 years). In subjects with ONbp (n¼677), a U-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…These 3 studies comprised male participants only and relied on a single cross‐sectional assessment of alcohol consumption. To our knowledge, only 1 study of the association between alcohol and changes in PWV has used repeat assessments of alcohol consumption . This study found that moderate drinkers with normal blood pressure had significantly smaller increases in PWV over 6 years than did nondrinkers.…”
Section: Introductionmentioning
confidence: 65%
“…These 3 studies comprised male participants only and relied on a single cross‐sectional assessment of alcohol consumption. To our knowledge, only 1 study of the association between alcohol and changes in PWV has used repeat assessments of alcohol consumption . This study found that moderate drinkers with normal blood pressure had significantly smaller increases in PWV over 6 years than did nondrinkers.…”
Section: Introductionmentioning
confidence: 65%
“…Smoking 107) , heavy drinking 108,109) , sedentary lifestyle 110) , and weight gain 111) have been shown to increase arterial stiffness, and lifestyle modifications exert beneficial effects on the arterial stiffness induced in patients with increased arterial stiffness induced by these factors 107,112,113) .…”
Section: Is Brachial-ankle Pwv Useful For Risk Stratification For Carmentioning
confidence: 99%
“…Studies have suggested a potentially protective effect of alcohol on vascular function (29) but it is more likely that this is a U-shaped relationship with detrimental effects at excessive levels (30). Subjects did attend visits fasted, including abstaining from alcohol from the preceding night, however longer term effects of alcohol on vascular reactivity would not be mitigated by this.…”
Section: Discussionmentioning
confidence: 99%